Community Perspective and Implications for Law Enforcement in Indonesia: A Sociological Study of Law - Nanda Rey Cakrawala; Evi Dwi Hastri; Merlin Cahyaningtias; M. Raofiqin Drajat (Res Judicata Law Review, 2024)
This article examines the public's perspective on law enforcement in Indonesia and its implications for the effectiveness of the legal system. With a sociological approach to law, this study aims to identify how public views regarding weaknesses in law enforcement affect trust and compliance with the law. Using sociolegal legal research, which is a type of approach in legal research that integrates the analysis of laws and regulations and legal doctrine with the study of social phenomena that interact with and are influenced by law. The results show that there is significant dissatisfaction among the community related to the implementation of the law, which is often considered inconsistent and unfair. Public perceptions of corruption, slow legal processes, and law enforcement's inability to handle cases effectively contribute to a decline in trust in the legal system. Implications of these findings include the urgent need for more transparent and accountable legal reforms, as well as increasing the capacity of law enforcement agencies to meet public expectations. This study concludes that improving law enforcement requires an approach that involves active participation from the community as well as increasing integrity and professionalism in legal institutions. Key recommendations include strengthening social control mechanisms, increasing training for law enforcement, and implementing a transparency system to improve the relationship between law and society.